Inhibition of myeloid differentiation primary response protein 88 provides neuroprotection in early brain injury following experimental subarachnoid hemorrhage. Issue 1 (December 2017) - Yan, Huiying; Zhang, Dingding; Wei, Yongxiang; Ni, Hongbin; Liang, Weibang; Zhang, Huasheng; Hao, Shuangying; Jin, Wei; Li, Kuanyu; Hang, Chun-Hua
Abstract Accumulating of evidence suggests that activation of nuclear factor-kappa B (NF-κB) and mitogen-activated protein kinases (MAPKs) exacerbates early brain injury (EBI) following subarachnoid hemorrhage (SAH) by provoking pro-inflammatory and pro-apoptotic signaling. Myeloid differentiation primary response protein 88 (MyD88) is an endogenous adaptor protein in the toll-like receptors (TLRs) and interleukin (IL) -1β family signaling pathways and acts as a bottle neck in the NF-κB and MAPK pathways. Here, we used ST2825, a selective inhibitor of MyD88, to clarify whether inhibiting MyD88 could provide neuroprotection in EBI following SAH. Our results showed that the expression of MyD88 was markedly increased at 24 h post SAH. Intracerebroventricular injection of ST2825 significantly reduced the expression of MyD88 at 24 h post SAH. Involvement of MAPKs and NF-κB signaling pathways was revealed that ST2825 inhibited SAH-induced phosphorylation of TAK1, p38 and JNK, the nuclear translocation of NF-κB p65, and degradation of IκBα. Further, ST2825 administration diminished the SAH-induced inflammatory response and apoptosis. As a result, SAH-induced EBI was alleviated and neurological deficits caused by SAH were reversed. Our findings suggest that MyD88 inhibition confers marked neuroprotection against EBI following SAH. Therefore, MyD88 might be a promising new molecular target for the treatment of SAH.